E-Learning during COVID-19 pandemic; Turning a crisis into opportunity: A cross-sectional study at The University of Jordan. (October 2021) - Bani Hani, Amjad; Hijazein, Yazan; Hadadin, Hiba; Jarkas, Alma K.; Al-Tamimi, Zahraa; Amarin, Marzouq; Shatarat, Amjad; Abu Abeeleh, Mahmoud; Al-Taher, Raed
Abstract: Objectives: To assess the medical students' satisfaction and knowledge attainment through distant learning during the COVID-19 pandemic. Methods: This is a cross-sectional, self-reported, questionnaire-based study that was conducted at the School of Medicine at the University of Jordan in April 2020. The targeted population was the students at the school of medicine. An online questionnaire was created using Google Forms. Satisfaction and knowledge attainment among students were assessed using independent-samples t -test. Results: A total of 1000 medical students completed the survey, 506 (50.6%) basic science students and 494 (49.4%) were clinical science students. 655 (65.5%) of all students were either satisfied or neutral with e-learning. 63.6% of basic science students and 59.5% of clinical students stated that they gained and understood knowledge in the same way as or better than they did before initiation of exclusive e-learning. Satisfaction and knowledge gain were significantly affected by student preparedness (p < 0.000), teacher performance (p < 0.000), and website accessibility (p < 0.000). Conclusion: Transition from traditional in-class teaching to distant learning, whether full or blended, is an inevitable step. In our sample, students were generally satisfied with e-learning and the knowledge attained using it. There was a significant relation between satisfaction and attainment and preparedness of students, teachers, and the medical school. Highlights: There is a difference in student's satisfaction from e-learning between basic science students and clinical students. Teachers' performance, and Accessibility to websites had a significant impact on student satisfaction. Students' experience in using e-learning platforms and websites, also had a significant impact on student satisfaction. 76.3% of all the students believe that the electronic devices did not cause any financial burden. The most popular devices used to connect to the internet were mobile phones and laptops.